Transferts culturels, urgence historique et pratiques artistiques - Hélène Beauchamp (Mélanges de la Casa de Velázquez, 2008)
This article examines a species of «circumstantial» cultural transfer. It shows that numerous manifestations of agitation and propaganda in the form of teatro de guerra organised by the Republican side during the Spanish Civil War were in fact the product of a cultural transfer forged under the pressure of war: from Russian (and later Soviet) and German experiences in «agitprop» theatre in the 1920s. After first retracing the evolution of this form of political theatre the author shows how in Spain it was appropriated and adapted to the immediate requirements of the conflict and to the audiences for whom it was intended. Popular puppet theatre in this context contributed particularly to the success of this appropriation as a «common platform». The author concludes by questioning how permanent this transfer was, whether a practice responding to political circumstances or an artistic practice with a more durable presence in Spanish dramatic creation.